2008
DOI: 10.1111/j.1439-0531.2007.00973.x
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy‐Associated Glycoprotein Secretion in North Moroccan Goats

Abstract: The plasma profile of pregnancy-associated glycoprotein (PAG) and its relationship with fetal number were studied in 14 North Moroccan goats using a semi-heterologous radioimmunoassay (RIA). Peripheral blood was collected every day during the first month of pregnancy, afterward the blood samples were collected trice a week. The PAG were first detected at day 20 of pregnancy, their levels increase to week 8 of gestation then decrease slightly until parturition. Statistical differences between goats carrying one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
(50 reference statements)
0
3
2
1
Order By: Relevance
“…This is consistent with our current results, with the difference that each of the PAGs and P 4 reached their highest average on day 88 after mating, then began to decrease slowly and gradually until the date of birth. On the other hand, the PAG and P 4 levels in our data were different from those reported by González et al (2004) and Chentouf et al (2008). We attribute this to the homologous or heterologous goat breed variants that affect P 4 synthesis, and this re ects the genetic strategy for maintaining a pregnancy under severe conditions (Sousa et al, 1999).…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…This is consistent with our current results, with the difference that each of the PAGs and P 4 reached their highest average on day 88 after mating, then began to decrease slowly and gradually until the date of birth. On the other hand, the PAG and P 4 levels in our data were different from those reported by González et al (2004) and Chentouf et al (2008). We attribute this to the homologous or heterologous goat breed variants that affect P 4 synthesis, and this re ects the genetic strategy for maintaining a pregnancy under severe conditions (Sousa et al, 1999).…”
Section: Discussioncontrasting
confidence: 89%
“…Moreover, in native North Moroccan goats. Chentouf et al (2008) observed statistical differences between goats carrying one or two foetuses. Vasques et al (1995) proposed the relationship between fetal growth rate and PAGs increase during pregnancy in cows as the important decline in PAG1 was re ected by stopped trophectoderm development.…”
Section: Discussionmentioning
confidence: 85%
“…(2000) found that in goat that delivered twin foetuses had higher cPAGs concentrations than those that delivered single foetus. Moreover, in native North Moroccan goat, Chentouf et al. (2008) observed statistical differences between goats carrying one or two foetuses.…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, the evaluation of PAG plasma concentration in does serve as an indicator for early pregnancy detection (Shahin et al, 2013) and also in ewes (El Amiri et al, 2015). It allowed for accurate prediction of pregnancy starting from 21 days after breeding and beyond (Green et al, 2005), and also to estimate the embryo/fetal count in dairy goats (Chentouf et al, 2008). It can be measured by radioimmunoassay (RIA) (Zoli et al, 1992) and ELISA (Green et al, 2005).…”
Section: Introductionmentioning
confidence: 99%